The General Clauses Act (X of 1897) - Bangladesh; Dhaka Law Reports (Firm) (Dhaka : Dhaka Law Reports, 2007)
With upto date amendments including case laws.
Includes index.
English and Bengali.
Keywords: Law -- Bangladesh -- Interpretation and construction; Statutes -- Bangladesh -- Language; Delegated legislation -- Bangladesh -- Language